Formation of the Tatar nation and development stages of its nationhood (before 1917). - Rafael S. Khakimov (Историческая этнология, 2019)
The article focuses on the process of the Tatar people’s transformation into the contemporary nation. The analysis of the development of Tatars’ nationhood has been conducted on a staged basis, beginning from uncovering Tatars’ relation to the Scythian culture and ending with the exaluation if the tatar ethnos situation in the Russian Empire period. The author examines two ways of nation formation – European “vertical” and “nomad” “horizontal.” The path of the Tatar nation formation lies within the framework of the “nomadic” civilization development. Based on the results of genetic, archeological and linguistic research, both the common ground and particular features have been revealed in the establishment of ethnic borders and development of the Tatar culture.